IDENTIFYING ENGLISH LANGUAGE NEEDS OF RELIGIOUS GUIDES AT THE GENERAL PRESIDENCY OF THE GRAND MOSQUE AND PROPHET’S MOSQUE - Aljadani, Mahmoud; Alsolami, Turki (ETERNAL (English, Teaching, Learning, and Research Journal), 2020)
This study aims at identifying English language needs for religious guides at The General Presidency of The Grand Mosque and Prophet’s Mosque. This study adopted a quantitative approach methodology using needs analysis questionnaire. The quantitative data collection instrument was a questionnaire with (51) participants. SPSS was used as the quantitative data analysis method. Findings showed that listening and speaking were the most important skills, and reading was moderately important, while writing is not important at all. Also, English is greatly rated as a tool to effectively perform their tasks in term of preaching and advising guests and pilgrims. Difficulties are embodied in lacking English language, accents, and proper religious expressions and vocabulary. This study highlights an urgent need for English for Religious Purposes. The study proposes a general guideline for a course design framework based on participants’ needs.